Creating good citizen through company ethical values - Anggraeni, Ade Irma (Penerbit Universiti Kebangsaan Malaysia, 2014)
Creating high employee engagement is becoming more important in achieving sustainability in small and medium enterprises (SMEs). It helps organisations to motivate their employees to go beyond expectation. The main characteristic of organisation that pursues sustainability includes creating ethical values through organisational climate. This paper analyses the impact of ethical work climate on employee engagement and organisational citizenship behavior (OCB). Study was conducted on SMEs in Central Java, Indonesia. This research utilised quantitative approach and data collection was based on survey questionnaire. The result highlighted the significant impact of ethical work climate on employee engagement and OCB. This study’s findings contribute to the business ethics and SME literature by providing relevant empirical evidence based on primary data. The results provide guidance to SMEs in achieving sustainability.